A method for testing the anti-pollution performance of adhesive layer materials for roads and bridges

By spreading contaminants on the surface of the adhesive layer material and simulating construction conditions for testing, the pollutant residue ratio of the adhesive layer material is calculated, and the problem of lack of effective anti-pollution performance testing methods in the prior art is solved, and scientific material selection and performance evaluation are achieved.

CN115201418BActive Publication Date: 2025-03-14ANHUI TRANSPORTATION HLDG GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210827314.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-13
Publication Date
2025-03-14
Estimated Expiration
2042-07-13

AI Technical Summary

Technical Problem

The prior art lacks effective testing methods for the anti-pollution performance of adhesive layer materials, resulting in blindness in the material selection process and the scientific evaluation of anti-pollution performance of adhesive layer materials.

Method used

A method for anti-pollution performance testing of adhesive layer materials for road bridges is provided. By spreading pollutants on the surface of adhesive layer materials, simulating on-site construction conditions, conducting insulation, rolling and cleaning, and calculating pollutant residue ratio to evaluate the anti-pollution performance of adhesive layer materials.

Benefits of technology

Through this test method, the anti-pollution performance of the adhesive layer material can be scientifically evaluated, the gap in the test methods in the prior art is filled, the problem of blindness in material selection is solved, and the accuracy of the test results is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115201418B_ABST
    Figure CN115201418B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of road and bridge engineering, and specifically to a method for testing the anti-pollution performance of adhesive layer materials for roads and bridges. The method provided in the present application simulates the actual contamination of the adhesive layer in the engineering, spreads pollutants on the surface of the adhesive layer material, and performs heat preservation, rolling and cleaning, calculates the residual ratio of pollutants on the surface of the adhesive layer material, and evaluates the anti-pollution performance of the adhesive layer material, thereby filling the gap in the testing method in the prior art, solving the problem of blind material selection caused by the inability to scientifically test the anti-pollution performance of the adhesive layer material, and improving the performance evaluation system of the adhesive layer material, so as to facilitate the guidance of operating personnel to scientifically identify the material performance and select the material according to the engineering needs, which is of great significance for the durability and improvement of the performance of road and bridge pavements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road engineering, and in particular to a method for testing the anti-pollution performance of an adhesive layer material for roads and bridges. Background Art

[0002] The tack layer plays an important role in bonding the layered structure into a whole in asphalt pavement. The bonding effect of the tack layer depends not only on the bonding performance of the material, but also on its anti-pollution ability. In the actual construction process, the upper structure cannot be laid in time after the tack layer is spread. During the period of exposure, the tack layer may be polluted by the environment and construction. The failure of the pavement structure layer due to tack layer pollution is one of the direct causes of road diseases. In order to solve the problem of tack layer materials being easily polluted, the relevant industry has developed various special anti-pollution tack layer materials, including non-stick wheel emulsified asphalt.

[0003] After investigation, it was found that the material evaluation of the above-mentioned special anti-pollution tack coat materials still uses the conventional tack coat emulsified asphalt evaluation system. In addition to the material performance evaluation itself, the composite shear test and pull-out test of the tack coat materials are added to the road performance evaluation, but the evaluation of the anti-pollution performance of the tack coat materials themselves is lacking. For example, the literature material "Experimental Study on Factors Influencing the Bonding Performance of Asphalt Pavement Interlayers" [J] (He Rui, Wu Shuhua, et al. Sino-Foreign Highway. 2015, 35 (4): 272-276) studied the factors affecting the bonding performance of pavement interlayers, including "the influence of interlayer pollution on bonding performance", but it explored the influence of different pollutants and different pollution degrees on the bonding performance of pavement, which still belongs to the research and evaluation of road performance, rather than the anti-pollution performance of the tack coat materials themselves. Therefore, due to the lack of research on tack coat materials in the prior art, the anti-pollution performance of the tack coat materials, which is a key concern, cannot be quantified and presented, and it is impossible to intuitively guide the operators to select the tack coat materials according to the construction site environment.

[0004] Therefore, developing a test method for the anti-pollution performance of adhesive materials for roads and bridges is of great significance for improving the material evaluation system and guiding users to scientifically identify material performance. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and to provide a method for testing the anti-pollution performance of tack coat materials for roads and bridges, to simulate on-site construction conditions, to spread pollutants on the surface of the tack coat material, to clean it after thermal rolling, to calculate the residual ratio of pollutants on the surface of the tack coat material, to evaluate the anti-pollution performance of the tack coat material, to fill the gap in the testing method in the prior art, and to solve the problem of blind material selection caused by the inability to scientifically test the anti-pollution performance of the tack coat material.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for testing the anti-pollution performance of a road and bridge adhesive layer material comprises the following steps:

[0008] S1. Sprinkle the adhesive layer material to be tested on the rutting board, and after the adhesive layer material is fully stabilized, it forms a test base surface together with the rutting board, and weigh the mass m0 of the test base surface;

[0009] S2. Sprinkle pollutants on the surface of the adhesive layer material to form a polluted area, and record the mass m1 of the test base surface after spreading the pollutants;

[0010] S3. Insulation test base surface, rolling contaminated area after insulation completion;

[0011] S4. Clean the test surface and weigh the mass m2 of the cleaned test surface;

[0012] S5. Calculate the pollutant residual ratio γ, the calculation formula is as follows:

[0013]

[0014] Where m0 is the mass of the test surface, g; m1 is the mass of the test surface after spreading the pollutants, g; m2 is the mass of the test surface after cleaning, g.

[0015] The smaller the pollutant residual ratio γ value is, the better the anti-pollution performance of the adhesive layer material is.

[0016] The difference between this application and the prior art is that

[0017] The existing technologies all form tack layer materials into pavement structures to test their road performance, while the testing method provided in the present application can specifically evaluate the anti-pollution performance of tack layer materials. There is no need to form the tack layer materials into pavement structures. The test can be carried out by simply sprinkling them on the surface of the rutting plate. The on-site construction conditions are simulated by heat preservation, rolling and cleaning, which effectively improves the accuracy of the test results. Construction personnel can understand the anti-pollution performance of the tack layer materials based on the test results, which is convenient for selecting the tack layer materials during construction.

[0018] Preferably, in step S1, the mixture type of the rutting plate is the same as the mixture type of the corresponding structural layer at the construction site; and the spreading amount of the adhesive layer material is the same as the spreading amount at the construction site.

[0019] Preferably, in step S2, the contaminated area formed after the pollutant is spread is rectangular, whose length is the same as the side length of the test base surface, and whose width is 1 / 3 of the side length of the test base surface, and the contaminated area is located in the center of the test base surface; further preferably, the amount of pollutant spread is controlled to completely cover the contaminated area but without producing an obvious floating layer.

[0020] The contaminated area of ​​the pollutants is controlled to be located in the central area of ​​the test base surface. Experimental verification shows that testing within this area is sufficient to prove the anti-pollution performance of the adhesive layer material. At the same time, if the pollutants are spread all over the test base surface, there will be dead corners that cannot be rolled during the rolling process, which not only wastes manpower and material resources, but also cannot guarantee the test effect, resulting in discrepancies between the test results and the actual anti-pollution performance of the adhesive layer material.

[0021] Preferably, in step S2, the pollutants are composed of type I sand, type II sand and dust, the particle size range of type I sand is 0.6mm-1.18mm, the particle size range of type II sand is 0.3mm-0.60mm, the particle size range of dust is <0.3mm, and the mass ratios of type I sand, type II sand and dust in the pollutants are 10%-15%, 20%-25% and 60%-70% respectively; further preferably, the detailed parameters of type I sand, type II sand and dust in the pollutants are shown in Table 1:

[0022] Table 1 Detailed parameters of each component in the pollutants

[0023]

[0024] Preferably, in step S3, the insulation temperature is the temperature of the asphalt pavement at the highest temperature in summer at the project site, and the insulation time is ≥5h.

[0025] Preferably, in step S3, during the insulation process, the temperature accuracy control range is ≤0.1°C; further preferably, the insulation equipment is a constant temperature box used in a rutting test.

[0026] Preferably, in step S3, the equipment used in the process of rolling the polluted area is a rutting tester, the applied pressure is 0.7 MPa, the rolling times are 2 back and forth, and the polluted area is rolled 4 times in total. Under high temperature conditions, pollutants are rolled by vehicles and will be more difficult to clean. This step is set to strict test conditions and more stringent material screening.

[0027] Preferably, in step S4, the steps of cleaning the test base surface are: ① use a brush to clean all pollutants; ② use a hair dryer to blow away pollutants in the structural depth; ③ use a brush to clean again. This step simulates the cleaning steps commonly used after the adhesive layer material is contaminated at the engineering site, so as to further meet the site conditions.

[0028] The beneficial effects of the present invention are:

[0029] By simulating the actual tack layer contamination situation of the project, pollutants are spread on the surface of the tack layer material and then insulated, rolled and cleaned, the residual ratio of pollutants on the surface of the tack layer material is calculated, and the anti-pollution performance of the tack layer material is evaluated. This fills the gap in the testing method in the existing technology, solves the problem of blind material selection caused by the inability to scientifically test the anti-pollution performance of the tack layer material, and improves the performance evaluation system of the tack layer material, which is convenient for guiding operators to scientifically identify material performance and select materials according to project needs. It is of great significance to maintain and improve the durability of asphalt pavement performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of the test base surface and the contamination area of ​​the contaminants on its surface. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0032] Embodiment 1,

[0033] A method for testing the anti-pollution performance of a tack coat material for a road or bridge. In this embodiment, the tack coat material 1 tested is a common emulsified asphalt material, the mixture type of the rutting plate is AC-20, and the asphalt pavement temperature at the highest temperature in summer at the project site is 60°C. The specific steps are as follows:

[0034] S1. Sprinkle adhesive layer material on the rutting plate. The amount of adhesive layer material to be spread is consistent with the project site, which is 0.5kg / m 2 After the adhesive layer material is fully stabilized, it forms a test base surface together with the rutting plate. The mass m0 of the test base surface is weighed, which is 11079g;

[0035] S2. Sprinkle pollutants on the test surface. The polluted area of ​​the pollutants is rectangular, with a length equal to the side length of the test surface and a width equal to 1 / 3 of the side length of the test surface. Figure 1 As shown, the polluted area is located in the center of the test base surface, and the amount of pollutants spread is controlled to completely cover the polluted area but not produce a floating layer; the pollutants are composed of type I sand, type II sand and dust, and the mass m1 of the rutting plate and the test base surface after spreading the pollutants is recorded, which is 11120g; specifically, the specifications and proportions of type I sand, type II sand and dust in the pollutants are shown in Table 2:

[0036] Table 2 Composition of artificial pollutants

[0037]

[0038]

[0039] S3. Place the test base surface in the rutting test machine insulation box for 5 hours, the insulation temperature is 60°C, and the temperature accuracy is controlled within 0.1°C during the insulation process. After the insulation is completed, use the rutting test machine to roll the contaminated area on the test base surface, apply a pressure of 0.7MPa, roll back and forth 2 times, and roll the contaminated area 4 times in total;

[0040] S4. Clean the test surface, the steps are: ① use a brush to clean all contaminants; ② blow the contaminants in the structural depth with a hair dryer; ③ clean it again with a brush, and after cleaning, weigh the mass m2 of the test surface, which is 11088g;

[0041] S5. Calculate the pollutant residual ratio γ, the calculation formula is as follows:

[0042]

[0043] Wherein, m0 is the mass of the test surface, g; m1 is the mass of the test surface after spreading the pollutants, g; and m2 is the mass of the test surface after cleaning, g.

[0044] Substituting the above data, we get

[0045]

[0046] Embodiment 2:

[0047] A method for testing the anti-pollution performance of a tack coat material for a road or bridge. In this embodiment, the tack coat material 2 tested is an SBS modified emulsified asphalt material, the mixture type of the rutting plate is AC-20, and the asphalt pavement temperature at the highest temperature in summer at the project site is 60°C. The specific steps are as follows:

[0048] S1. Sprinkle adhesive layer material on the rutting plate. The amount of adhesive layer material to be spread is consistent with the project site, which is 0.5kg / m 2 After the adhesive layer material is fully stabilized, it forms a test base surface together with the rutting plate. The mass m0 of the test base surface is weighed to be 11088g;

[0049] S2. Sprinkle pollutants on the test surface. The polluted area of ​​the pollutants is rectangular, with a length equal to the side length of the test surface and a width equal to 1 / 3 of the side length of the test surface. Figure 1 As shown, the polluted area is located in the center of the test base surface, and the amount of pollutant spread is controlled to completely cover the polluted area but not produce a floating layer. The controlled spreading amount is the same as that of Experimental Example 1. The pollutants are composed of type I sand, type II sand and dust. Specifically, the specifications and proportions of type I sand, type II sand and dust in the pollutants are the same as those in Table 2. The mass m1 of the rutting board and the test base surface after spreading the pollutants is recorded as 11129g.

[0050] S3. Place the rutting plate and the test base surface in the rutting test machine insulation box for 5 hours, the insulation temperature is 60°C, and the temperature accuracy control range during the insulation process is ≤0.1°C. After the insulation is completed, use the rutting test machine to roll the contaminated area on the test base surface, apply a pressure of 0.7MPa, roll back and forth 2 times, and roll the contaminated area 4 times in total;

[0051] S4. Clean the test surface, the steps are: ① use a brush to clean all pollutants; ② blow the pollutants in the depth of the structure with a hair dryer; ③ clean it again with a brush, and after cleaning, weigh the mass m2 of the test surface, which is 11105g;

[0052] S5. Calculate the pollutant residual ratio γ, the calculation formula is as follows:

[0053]

[0054] Wherein, m0 is the mass of the test surface, g; m1 is the mass of the test surface after spreading the pollutants, g; and m2 is the mass of the test surface after cleaning, g.

[0055] Substituting the above data, we get

[0056]

[0057] Embodiment 3:

[0058] A method for testing the anti-pollution performance of a tack coat material for roads and bridges. In this embodiment, the tack coat material 3 tested is a non-stick wheel emulsified asphalt material, the mixture type of the rutting plate is AC-20, and the asphalt pavement temperature at the highest temperature in summer at the project site is 60°C. The specific steps are as follows:

[0059] S1. Sprinkle adhesive layer material on the rutting plate. The amount of adhesive layer material to be spread is consistent with the project site, which is 0.5kg / m 2 After the adhesive layer material is fully stabilized, it forms a test base surface together with the rutting plate. The mass m0 of the test base surface is weighed, which is 11081g;

[0060] S2. Sprinkle pollutants on the test surface. The polluted area of ​​the pollutants is rectangular, with a length equal to the side length of the test surface and a width equal to 1 / 3 of the side length of the test surface. Figure 1 As shown, the polluted area is located in the center of the test base surface, and the amount of pollutant spread is controlled to completely cover the polluted area but not produce a floating layer. The controlled spreading amount is the same as that of Experimental Example 1. The pollutants are composed of type I sand, type II sand and dust. Specifically, the specifications and proportions of type I sand, type II sand and dust in the pollutants are the same as those in Table 2. The mass m1 of the rutting board and the test base surface after spreading the pollutants is recorded as 11122g;

[0061] S3. Place the rutting plate and the test base surface in the rutting test machine insulation box for 5 hours, the insulation temperature is 60°C, and the temperature accuracy control range during the insulation process is ≤0.1°C. After the insulation is completed, use the rutting test machine to roll the contaminated area on the test base surface, apply a pressure of 0.7MPa, roll back and forth 2 times, and roll the contaminated area 4 times in total;

[0062] S4. Clean the test surface, the steps are: ① use a brush to clean all contaminants; ② blow the contaminants in the depth of the structure with a hair dryer; ③ clean it again with a brush, and after cleaning, weigh the mass m2 of the test surface, which is 11084g;

[0063] S5. Calculate the pollutant residual ratio γ, the calculation formula is as follows:

[0064]

[0065] Wherein, m0 is the mass of the test surface, g; m1 is the mass of the test surface after spreading the pollutants, g; and m2 is the mass of the test surface after cleaning, g.

[0066] Substituting the above data, we get

[0067]

[0068] Experimental example:

[0069] The anti-pollution performance of the adhesive layer material was tested by taking the adhesive layer materials 1-3 used in Examples 1-3 respectively. In order to verify the correlation between the pollutant residual ratio γ proposed in the present invention and the conventional road performance of the adhesive layer material, a comparative test was conducted. The specific steps are as follows:

[0070] (1) After the pollutant residual ratio γ of Example 1, Example 2 and Example 3 is tested, the composite rutting plate is formed with the lower structure, and the upper structure mixture type is SMA-13 ​​to form a composite part;

[0071] (2) The same upper and lower layer mixtures as in Examples 1-3 were used to form composite rutting plates (i.e., composite parts), and the tack layer materials were selected from ordinary emulsified asphalt, SBS modified emulsified asphalt, and non-stick wheel modified emulsified asphalt (i.e., tack layer materials 1-3 used in Examples 1-3), and the spraying amount was the same as in Examples 1-3 to ensure that the tack layer was not contaminated, and they were recorded as Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively;

[0072] (3) Core samples were drilled from the pollutant spreading locations of Examples 1, 2, and 3, and core samples were drilled from the same locations of Comparative Examples 1, 2, and 3 to test the pull-out strength and shear strength of the composite parts at 25°C. The test results are as follows:

[0073]

[0074]

[0075] In the above experimental data, the determination methods of the pull-out strength and shear strength of the composite parts all adopt the method given in Jiangsu Local Standard DB32 / T 2285-2012 "Technical Specifications for Construction of Water-Based Epoxy Asphalt Waterproof Adhesive Layer on Cement Concrete Bridge Deck". Composite part pull-out strength ratio = pull-out strength measured in the embodiment / pull-out strength measured in the corresponding proportion × 100%, composite part shear strength ratio = shear strength measured in the embodiment / shear strength measured in the corresponding proportion × 100%.

[0076] According to the experimental data measured in the table, after correlation test, the correlation coefficient between the composite pull-out strength ratio and the pollutant residual ratio γ is -0.88, and the correlation coefficient between the composite shear strength ratio and the pollutant residual ratio γ is -0.90, indicating that after the bonding material forms the pavement structure, its main road performance indicators, the composite pull-out strength and the composite shear strength, are highly negatively correlated with the pollutant residual ratio γ, that is, the smaller the pollutant residual ratio γ, the more the road performance of the bonding material can be guaranteed.

[0077] The above experiments and experimental data prove that the data measured by the anti-pollution performance testing method of the adhesive layer material provided in this application is consistent with the performance of the adhesive layer material itself, and can be used to guide construction personnel in selecting adhesive layer materials during the construction process.

[0078] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A method for testing the anti-pollution performance of adhesive layer materials for roads and bridges, characterized in that: The steps include: S1. Sprinkle the adhesive layer material to be tested on the rutting board, and after the adhesive layer material is fully stabilized, it forms a test base surface together with the rutting board, and weigh the mass m0 of the test base surface; S2. Sprinkle pollutants on the surface of the adhesive layer material to form a polluted area, and record the mass m1 of the test base surface after spreading the pollutants; S3. Insulation test base surface, rolling contaminated area after insulation completion; S4. Clean the test surface and weigh the mass m of the cleaned test surface. 2; S5. Calculate the pollutant residual ratio , the calculation formula is as follows: Where m0 is the mass of the test surface, g; m1 is the mass of the test surface after spreading the pollutants, g; m2 is the mass of the test surface after cleaning, g. Residual pollutant ratio The smaller the value, the better the anti-pollution performance of the adhesive layer material.

2. The anti-pollution performance testing method of road and bridge adhesive materials according to claim 1, characterized in that: The type of mixture of the rutting plate is the same as the type of mixture of the corresponding structural layer at the engineering site; the spreading amount of the adhesive layer material is the same as the spreading amount at the engineering site.

3. The anti-pollution performance testing method of road and bridge adhesive materials according to claim 1, characterized in that: In the step S2, the polluted area formed after the pollutants are spread is rectangular, the length of which is the same as the side length of the test base surface, the width of which is 1 / 3 of the side length of the test base surface, and the polluted area is located in the center of the test base surface.

4. The method for testing the anti-pollution performance of the adhesive layer material for roads and bridges as claimed in claim 1, characterized in that: In step S2, the pollutants are composed of type I sand, type II sand and dust, the particle size range of the type I sand is 0.6mm~1.18mm, the particle size range of the type II sand is 0.3mm~0.60mm, the particle size range of the dust is <0.3mm, and the mass ratios of the type I sand, type II sand and dust in the pollutants are 10%~15%, 20%~25% and 60%~70% respectively.

5. The method for testing the anti-pollution performance of adhesive layer materials for roads and bridges as claimed in claim 1, characterized in that: In step S3, the insulation temperature is the temperature of the asphalt pavement at the highest temperature in summer at the project site, and the insulation time is ≥5h.

6. The method for testing the anti-pollution performance of adhesive layer materials for roads and bridges as claimed in claim 1, characterized in that: In the step S3, during the heat preservation process, the temperature accuracy is controlled within a range of ≤0.1°C.

7. The method for testing the anti-pollution performance of the adhesive layer material for roads and bridges as claimed in claim 1, characterized in that: In the step S3, the equipment used in the process of rolling the polluted area is a rutting tester, the applied pressure is 0.7 MPa, the rolling times are 2 back and forth, and the polluted area is rolled 4 times in total.

8. The method for testing the anti-pollution performance of adhesive layer materials for roads and bridges as claimed in claim 1, characterized in that: In step S4, the steps of cleaning the test base surface are: ① using a brush to clean all pollutants; ② using a hair dryer to clean pollutants within the structural depth; ③ Clean again with a brush.

Citation Information

Patent Citations

  • Device for detecting easily-cleaning property of ceramic by using oil residue method

    CN102928312A

  • Method for testing and evaluating properties of bonding layer of asphalt pavement

    CN107817213A